Embodied Interaffectivity in the Emergence and Maintenance of Group Cohesion - Jones, Cheryl; Pino-Pasternak, Deborah; Volet, Simone (Frontiers in Psychology, 2022)
Group cohesion is an affect-laden construct, with a large body of research indicating its importance for success of teams. Surprisingly, it has received scant attention in collaborative learning contexts, and little is known about its development as dynamically emergent in the spontaneous, interdependent actions of actors during groupwork. This paper details an illustrative case analysis which took an embodied perspective to explore the role of interaffectivity in the emergence and maintenance of cohesion in one small group of university students who reported a highly positive and productive experience of collaborative science activities over a semester. The case analysis made visible group cohesion as unfolding and enactive in the myriad ephemeral and seemingly inconsequential microlevel behaviors that evolved into macro-temporal patterns of positive embodied interaffectivity, magnifying their visibility and collective impact. A fine-grained embodiment lens unveiled how participants cocreated collaborative affordances in actions that involved corporeal orientation as well as use of space, task, and other material artifacts. Task-related humor within routine task interaction offered the potential for establishing group cohesion in early group life, but also posed a potential threat to task-focused cohesiveness, requiring careful modulation at critical task points. Attentiveness not only to the task but importantly, to one another as interpersonal attentiveness, appeared to be a key factor in developing and maintaining group cohesion, also demonstrating collaborative learning as a process of orienting to and understanding tasks through one another. An embodiment lens highlighted mutual attentiveness in the ongoing orienter-orientee microprocesses that facilitated group orientation early in group life, and in reorienting to positive embodied interaffectivity when the group reconvened for their joint science activities in subsequent weeks.